Sustainable lunch programs: educational foodservice’s sustainability efforts and school nutrition - Zoeller, Rowan (Kansas State University, 2020)
This report examines the relationship between farm-to-school initiatives and environmental sustainability within the dietary and nutritional constructs of the National School Lunch Program (NSLP) and Healthy, Hunger-Free Kids Act (HHFKA). Farm-to-school programs and other hands-on nutritional and agricultural education initiatives can improve compliance with the strict nutrition and dietary guidelines of the NSLP and HHFKA. Innovations in the farm-to-school movement, including sourcing local produce, increasing scratch cooking, using more fresh ingredients, and increasing hands-on nutrition and agricultural education, can increase a school’s environmental sustainability. These activities demonstrate the benefits farm-to-school program involvement has on student nutritional intake and dietary habits. Potential environmental benefits of farm-to-school programs include reducing food waste, decreasing long-distance travel, cutting down on packaged and preprocessed foods, and/or creating new green spaces. Chicago Public Schools’ current healthy food, farm-to-school, and sustainability initiatives are highlighted in this report. Using the Kansas State University online research database, recent articles studying nutrition education, farm-to-school innovations, school gardens, and cafeteria sustainability were identified. Studies were chosen based on their emphasis on NSLP participation and adherence to current dietary guidelines and standards, including the HHFKA and direct or indirect environmental benefits.
Keywords: National School Lunch Program (NSLP); Farm to school; School lunch; Healthy, Hunger-Free Kids Act (HHFKA); Foodservice sustainability